2017
DOI: 10.1186/s13014-017-0941-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor treating fields (TTFields) delay DNA damage repair following radiation treatment of glioma cells

Abstract: BackgroundTumor Treating Fields (TTFields) are an anti-neoplastic treatment modality delivered via application of alternating electric fields using insulated transducer arrays placed directly on the skin in the region surrounding the tumor. A Phase 3 clinical trial has demonstrated the effectiveness of continuous TTFields application in patients with glioblastoma during maintenance treatment with Temozolomide. The goal of this study was to evaluate the efficacy of combining TTFields with radiation treatment (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 30 publications
6
136
0
Order By: Relevance
“…This downregulation of FA genes was accompanied by slower DNA repair postradiation and a greater number of residual (unrepaired) DNA lesions at 48 hours. This was confirmed by Giladi et al, who also described a synergistic enhancement of efficacy when TTFields was used in combination with ionizing radiation (IR) in glioma cells 16 including the impairment of radiation-or chemically-induced DNA damage repair. However, while monitoring DSB repair kinetics after IR followed immediately by TTFields exposure, it was noted that the number of g-H2AX foci was substantially greater than that of g-H2AX-53BP1 co-localized foci.…”
Section: Translational Significancementioning
confidence: 71%
“…This downregulation of FA genes was accompanied by slower DNA repair postradiation and a greater number of residual (unrepaired) DNA lesions at 48 hours. This was confirmed by Giladi et al, who also described a synergistic enhancement of efficacy when TTFields was used in combination with ionizing radiation (IR) in glioma cells 16 including the impairment of radiation-or chemically-induced DNA damage repair. However, while monitoring DSB repair kinetics after IR followed immediately by TTFields exposure, it was noted that the number of g-H2AX foci was substantially greater than that of g-H2AX-53BP1 co-localized foci.…”
Section: Translational Significancementioning
confidence: 71%
“…When the initiation of TTFields was delayed until the end of RT treatment, the overall treatment efficacy diminished. This suggests that TTFields radiosensitized cancer cells, which may provide a therapeutic advantage in treating RT-resistant glioma cells (16). Exposing cells to TTFields immediately following ionizing radiation resulted in increased chromatid aberrations and a reduced capacity to repair DNA double-strand breaks, suggesting that TTFields induce a state of "BRCAness, " leading to enhanced sensitivity to ionizing radiation, which underscored a rationale for the use of TTFields combined with RT (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this population included patients with early disease progression; these patients were excluded from the EF-14 study. Preclinical studies demonstrated the rationale for combining TTFields with RT to treat GBM (16,17). In vitro TTFields plus RT has synergistic antimitotic effects, which lead to increased mitotic catastrophe in GBM cells via inhibition of cell survival, regulation of cell cycle, and hindering of DNA repair (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations